Nanostructuring of Additively Manufactured 316L Stainless Steel via High-Pressure Torsion for Enhanced Strength and Corrosion Performance - Mohd Yusuf, Shahir; Gao, Nong (International Journal of Integrated Engineering, 2024)
Bulk nanostructured materials (BNM) are defined as metallic materials with grain sizes <100 nm, and are known to possess superior mechanical and functional properties compared to those with grain sizes in the micron and millimeter ranges. In this study, high-pressure torsion (HPT), a nanostructuring approach that imposes compressive stress and extreme torsional strain on bulk materials is applied to an additively manufactured (AM) 316L stainless steel (316L SS) for 10 revolutions. The grain sizes, hardness, and corrosion performance before and after HPT are evaluated by using extensive microscopy techniques, Vickers hardness (HV) measurements, and electrochemical tests conducted in 3.5 wt.% NaCl solution, respectively. The results show that after 10 HPT revolutions, nano-sized grains (average: 42 nm) are obtained, whereas a three-fold increase in HV values from 220 HV to 600 HV are observed. Furthermore, the corrosion performance is also significantly enhanced as indicated by the reduction in corrosion rate from 2.53 µm/year initially, to 0.48 µm/year after HPT processing. These results highlight the benefits of HPT in producing bulk nanostructured materials with remarkably high hardness and excellent corrosion performance, potentially useful for a myriad of applications.